The girl and the stars - Lawrence, Mark, 1966- (The first book of the ice, 2020)
"A stunning new epic fantasy series following a girl who is cast out by her people and must fight with everything she has to survive, set in the same world as Red Sister. In some children, the old blood shows, giving them strength, speed, and mystical power. In the cities of Abeth's Corridor, such children are prized. But on the vast ice plains of Abeth, those traits lead children to burn bright and die young, and the discipline of the priests is harsh. Any child who shows signs of the old races is cast into the Pit of the Missing, never to be seen again. Yaz is only sixteen, but she feels a burgeoning gift and she knows the next gathering will be her last--the priests see everything, and her aberrance will not be tolerated. But then she is spared and her brother is identified as one of the broken and cast down into the pit. Stunned, awash with guilt and grief, she flings herself in after him. She expects to find death. Instead she finds a sprawling, secret civilization, where survival is even less assured than on the ice plains. And she soon realizes that this underground empire revolves around a great truth--and an even greater evil--that puts all of Abeth in danger"--